HUNTERS’ AWARENESS AND ATTITUDES TOWARDS WILDLIFE CONSERVATION IN IJEBU-EAST LOCAL GOVERNMENT AREA, OGUN STATE, NIGERIA - A. A KAREEM; MAKINDE, B. O. & OLUSAKIN, A. M. (UNILAG Journal of Medicine, Science and Technology, 2020)
The decline in wildlife has been a great concern in Nigeria and even globally. One of the factors responsible for wildlife loss is the indiscriminate hunting operations of animals in the forest. One may attribute this indiscriminate act to unawareness and negative attitude of hunters towards wildlife conservation and its benefits.  This study investigated the awareness and attitudes of hunters from Ijebu-East Local Government Area to wildlife conservation. Survey research design was employed in carrying out this study. Twenty hunters with 20 -40 years of hunting experience were interviewed once at their monthly meeting. Qualitative approach (Narrative Analysis) was used to analyse the information obtained from the respondents. The interview showed that 90% of the hunters had average level of awareness and 75% had favourable disposition towards wildlife conservation.  It is, therefore, recommended that more enlightenment programmes on current wildlife conservation management information should be made available to the hunters periodically, by both the federal and state government.